2007
DOI: 10.1108/09653560710729811
|View full text |Cite
|
Sign up to set email alerts
|

Co‐ordinating humanitarian operations in peace support missions

Abstract: Purpose -This paper seeks to contribute to a more effective co-ordination of humanitarian operations by military and civilian organizations involved in a peace support mission in response to a complex emergency. Design/methodology/approach -The information processing view, in particular Galbraith's typology of generic mechanisms for achieving co-ordination, is taken as the theoretical framework. This framework is subsequently applied to the co-ordination of humanitarian operations by military and civilian orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 13 publications
0
42
0
Order By: Relevance
“…Pettit and Beresford (2005) also defend a humanitarian logistics framework combining military and NGO experience in cases of disaster relief and recovery. Military support for natural disasters are widely used due to the capacity and asset availability required to support the surge demands (Rietjens et al, 2007). Military organisations have the robustness to operate in harsh field conditions and are capable of 12-hour response operations on a large scale (Kov acs and Tatham, 2009).…”
Section: Immediate Response Phasementioning
confidence: 99%
See 1 more Smart Citation
“…Pettit and Beresford (2005) also defend a humanitarian logistics framework combining military and NGO experience in cases of disaster relief and recovery. Military support for natural disasters are widely used due to the capacity and asset availability required to support the surge demands (Rietjens et al, 2007). Military organisations have the robustness to operate in harsh field conditions and are capable of 12-hour response operations on a large scale (Kov acs and Tatham, 2009).…”
Section: Immediate Response Phasementioning
confidence: 99%
“…Therefore the doctrines of intended deployments in the past have been quite distinctive but over the last decade many military doctrines have included humanitarian doctrinal aspects (Rietjens et al, 2007;Australian Army, 2009;Barber, 2011). In natural disasters -the focus of this paper -the doctrines of a deployed military force and the humanitarian community are more aligned than a complex emergency where there are distinct differences (Cross, 2012;Heaslip et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Given the fundamental differences between commercial supply chains and humanitarian supply chains (Beamon, 2004;Kovács and Spens, 2007;Oloruntoba and Gray, 2006;Thomas and Kopczak, 2005;Van Wassenhove, 2006) and the similarities between humanitarian supply chains and military supply chains (Oloruntoba and Gray, 2006;Pettit and Beresford, 2005;Rietjens et al, 2007;Skoglund and Hertz, 2007;Tatham, 2006;Tysseland, 2007), a number of issues as presented in Table 1 have materialised. Kovács and Tatham (2009) demonstrated that both humanitarian and military supply chains in contrast to commercial supply chains have to plan to respond for what they view as inevitable events such as natural or complex disasters.…”
Section: Current Supply Chain Theory: Comparison Of Commercial Militmentioning
confidence: 99%
“…The need for better coordination according to Whiting and Ayala-Ostrom (2009) is particularly compelling due to the logistics expenditure consumes up to 40% of the total humanitarian aid budgets. Rietjens et al (2007) argue conflicting objectives between humanitarian organisations and military often leads to resource wastage as relief agencies and military units undertake similar operations. This duplication is not only prevalent between NGOs and military but also between different NGOs.…”
Section: Military Involvement In Humanitarian Logisticsmentioning
confidence: 99%
See 1 more Smart Citation